HSCT FOR HODGKIN LYMPHOMA - Paz, Alessandra; Bittencourt, Rosane; Lerner, Decio; Manca, Camila; Souza, Mair; Baiocchi, Otavio; Bachour, Philip; Melo, Leila Pessoa de; Nabhan, Samir Kanaan (JOURNAL OF BONE MARROW TRANSPLANTATION AND CELLULAR THERAPY, 2021)
THE BRAZILIAN SOCIETY FOR BLOOD AND MARROW TRANSPLANTATION (SBTMO) PRESENTS THE BRAZILIAN GUIDELINES ON HEMATOPOIETIC STEM CELL TRANSPLANTATION